Intervenção docente nos conflitos interpessoais de estudantes: formas e fatores de interferência - Ribeiro, Elvira Maria Portugal Pimentel (2018)
The forms of intervention carried out by the teachers through the conflicts that occur among the students differ due to the interference of some factors. From this observation comes up the following questions, which factors could interfere in the type of intervention that each teacher adopts? And how does this intervention occur? These questions led to the construction of this research which general objective is to understand the factors that can interfere in the teacher’s intervention in the face of the students' conflicts, and as specific objectives to identify the types of intervention used and considered as ideal by the teachers and to discuss about the difficulties encountered by them to intervene in the conflicts of the children. In order to achieve these objectives, a qualitative research was carried out through the case study of a municipal school in the city of Feira de Santana using the assumptions of moral development theory. The subjects were four teachers from the 3rd to the 5th year of elementary school, with which observations and interviews were made. The research was based on Piagetian theory of moral development, as well as the discussions of contemporary authors such as La Taille (1998; 2006), Puig (1998; 2004), Vinha (2000; 2003) and Tognetta (2009). The school conflicts were discussed from two dimensions, danger and learning opportunity (TOGNETTA; VINHA, 2011). The analysis of the data, showed up to the existence of five forms of teacher’s intervention, they are: the resolution of the conflict by the student, the preference of other contents instead of the conflict, the immediate containment of them, the mediation and the transfer of the conflict. Regarding the factors that interfere in the type of intervention chosen by the teacher, four were found, wich also represent some difficulties encountered by them to intervene. The first concerns the ambiguities of know-how in favor of autonomy. The second factor falls on children and families considered to be more difficult to cope with. The relationship between the sociomoral environment and the didactic time was the third interference factor found. The fourth factor refers to the representations that the teachers make of themselves, as to the intervention they perform in the face of conflicts. Thus, it is possible to conclude that each of the factors found can interfere of different way in the way the teachers make their interventions, being somehow interconnected. The continued education in service is an opportunity for teacher’s learning and transformation know-how-want-to-believe, to make that your tendency to intervention is more in favor of moral autonomy than heteronomy.